PROJECT-BASED TRAINING AS A MODERN TREND IN ENGINEERING EDUCATION - Raisa M. Petruneva; Olga V. Toporkova; Valentina D. Vasilyeva (Высшее образование в России)
The article considers the main trends in modern engineering activity which can become a basis for the RF educational policy formulation. The reasonswhy the Russian model of engineers’ professional training is lagging behind are shown with due consideration of the world trends. One of the main trends is the change in educational standards of engineer’s training focusing on project and managerial competences, and, correspondingly, project-based training (PBT). In the present state of things the in-depth examination of the accumulated experience and errors and a forecast of the future of engineering education are needed in order to address current and upcoming industry employment requirements.